The Effect of Electronic Word of Mouth and Price on The Purchase Decision of Big Banas Products in Makassar City - Moh. Rifky Wahyudi; Anwar Ramli; Muhammad Ilham Wardhana Haeruddin; Amiruddin Tawe; Muh. Ichwan Musa (PT. Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of electronic word of mouth and price on purchasing decisions for Big Bananas in Makassar City partially and simultaneously. The population in this study are followers of the Big Bananas Instagram account, totaling 78,182 users as of November 2022. The sample used is based on the slovin formula with an error rate of 10%, namely 100 respondents. The sampling withdrawal technique is systematic random sampling. Data collection techniques were carried out using questionnaires, literature studies and interviews. The data analysis technique used is multiple regression analysis using SPSS 22.00 for windows. The results showed that electronic word of mouth and price had a positive and significant effect on purchasing decisions for Big Bananas in Makassar City.